Stochastically stable implementation - Antonio Cabrales; Roberto Serrano (SERIEs - Journal of the Spanish Economic Association, 2012)
Restricting attention to economic environments, we study implementation under perturbed better-response dynamics (BRD). A social choice function (SCF) is implementable in stochastically stable strategies of perturbed BRD whenever the only outcome supported by the stochastically stable strategies of the perturbed process is the outcome prescribed by the SCF. For uniform mistakes, we show that any epsilon-secure and strongly efficient SCF is implementable when there are at least five agents. Extensions to incomplete information environments are also obtained.
Keywords: C72; D70; D78; 330; robust implementation; bounded rationality; evolutionary dynamics; mechanisms; stochastic stability; Beschränkte Rationalität; Unvollkommene Information; Nichtkooperatives Spiel; Stochastisches Spiel; Soziale Wohlfahrtsfunktion; Theorie